Response to 'A statistical evaluation of a 'stress-forecast' earthquake' by T. Seher & I. G. Main - Crampin, Stuart; Volti, Theodora; Stefánsson, Ragnar (Geophysical Journal International, 2004)
Seher & Main claim to make a statistical evaluation of successful stress-forecast of the time and magnitude of an earthquake in SW Iceland. A statistical evaluation of the data would be valuable, but unfortunately Seher & Main cannot do this as techniques have not yet been developed for the statistical analysis of discontinuous time-series within an overall continuous data set. Consequently, Seher & Main devise their own models of continuous time-series that are fundamentally different from those of our hypothesis. Seher & Main also briefly suggest several other concepts, which are serious misunderstandings of the stress-forecasting process. Consequently, their results and conclusions are unfortunately irrelevant to evaluating either the hypothesis or the stress-forecast.